PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI AMUNTAI HULU SUNGAI UTAR (STUDI KASUS TOKO KOSMETIK NABIL) - Agustina, Eka Santi; Muslimah , Muslimah (PPPM STIA Amuntai, 2020)
This study aims to determine the effect of service quality on customer satisfaction in Amuntai Hulu Sungai Utara (Case study of Nabil Cosmetics Shop). The analysis technique used is descriptive with a quantitative approach. Quantitative data in this study is in the form of ordinal from respondents' answers to the questions posed in the questionnaire. The t-statistic value of the path of the influence of the Responvenism variable on customer satisfaction in Amuntai Hulu Sungai Utara (Case study of Nabil Cosmetics Shop). is 2.562 which is greater than the normal distribution t-table of 1.96, meaning that there is a significant influence between the variable Responvenism and customer satisfaction, customer satisfaction in Amuntai Hulu Sungai Utara (Case study of Nabil Cosmetics Shop). responsive is the ability of a company that is carried out directly by employees to provide services quickly and responsively. The results showed that there was a positive and significant influence between the responveness factors on consumer satisfaction in Amuntai Hulu Sungai Utara (Case study of Nabil Cosmetics Shop). From the SPSS estimation results, another conclusion appears that the satisfaction model studied is actually only able to explain the phenomenon of consumer satisfaction in Amuntai Hulu Sungai Utara (Case study of Nabil Cosmetics Shop) of 68.9%. While the remaining 31.1% is explained by other variables which are not included in the model and error.